A novel 4‐DOF surgical instrument with modular joints and 6‐Axis Force sensing capability. Issue 1 (13th June 2016) - Li, Kun; Pan, Bo; Zhang, Fuhai; Gao, Wenpeng; Fu, Yili; Wang, Shuguo
Abstract: Background: It is difficult for surgeons to exert appropriate forces during delicate operations due to lack of force feedback in robot‐assisted minimally invasive surgery (RMIS). A 4‐DOF surgical grasper with a modular wrist and 6‐axis force sensing capability is developed. Methods: A grasper integrated with a miniature force and torque sensor based on the Stewart platform is designed, and a cable tension decomposition mechanism is designed to alleviate influence of the cable tension to the sensor. A modularized wrist consisting of four joint units is designed to facilitate integration of the sensor and eliminate coupled motion of the wrist. Results: Sensing ranges of this instrument are ±10 N and ±160 N mm, and resolutions are 1.2% in radial directions, 5% in axial direction, and 4.2% in rotational directions. An ex vivo experiment shows that this instrument prototype successfully measures the interaction forces. Conclusions: A 4‐DOF surgical instrument with modular joints and 6‐axis force sensing capability is developed. This instrument can be used for force feedback in RMIS. Copyright © 2016 John Wiley & Sons, Ltd.